Rewiring education how technology can unlock every student's potential - Couch, John D.; Towne, Jason (Tantor Audio, 2018)
Rewiring Education presents a bold vision for the future of education, looking at promising emerging technologies and how we--as parents, teachers, and voters--can ensure children are provided with opportunities and access to the relevant, creative, collaborative, and challenging learning environments they need to succeed.
Online resource; title from title details screen (OverDrive, August 6, 2019)
Keywords: Education -- Aims and objectives -- United States; Educational technology -- United States; Educational change -- United States; Technologie éducative; États-Unis; Enseignement; Réforme; États-Unis; COMPUTERS; General; Educational technology; Educational change; Education; Aims and objectives; United States; Downloadable audio books; Audiobooks; Livres audio